INCIDENCE OF METABOLIC SYNDROME IN THE URBAN POPULATION OF INDORE, M. P., INDIA - Agrawal, Jyoti; BHARIHOKE, NEELAM; KAR, ANAND (Innovare Journal of Medical Sciences, 2017)
ABSTRACT Background- The present study determines the prevalence of metabolic syndrome (MS), with special reference to hyperglycaemia and hyperlipidemia within urban population of a tertiary health care hospital in Indore (Madhya Pradesh), India. Material and method- This cross-sectional study involved 726 subjects (467 men & 259 women). MS was defined using revised National Cholesterol Education Program (NCEP) criteria. Results- When compared with the modified NCEP criteria, the prevalence of MS was found to be 7.51% (5.99% in men and 8.11% in women). Descriptive analysis exemplified a significantly increased mean values of FBS (P<0.01), PPBS (P<0.01) and lipid values (P<0.05) in the population. However, as compared to man, women showed significant elevated TCHO (P<0.05) and HDL (P<0.01). On the other hand, man exhibited increased TGL (P<0.05), cardiac risk ratio [C/H (P<0.01) and L/H (P<0.01)] than women. The highest prevalence of MS was seen in men of age group of 55-75 yrs and in women of age group of 20-34 yrs. Conclusion- Our test population showed an increased rate of hyperglycaemia and hyperlipidemia, with increase in age, indicating a need to implement policies to control this abnormal MS. Key words- Cardiac risk ratio, diabetes mellitus, fasting blood sugar, metabolic syndrome, serum cholesterolÂ 